Agile Processes in Software Engineering and Extreme Programming – Workshops: XP 2024 Workshops, Bozen-Bolzano, Italy, June 4–7, 2024, Revised Selected Papers - Marchesi, Lodovica; Goldman, Alfredo; Lunesu, Maria Ilaria; Przybyłek, Adam; Aguiar, Ademar; Morgan, Lorraine; Wang, Xiaofeng; Pinna, Andrea (Lecture Notes in Business Information Processing, 2025)
This open access book constitutes revised selected papers from the workshops held at the 25th International Conference on Agile Software Development, XP 2024, which took place in Bozen-Bolzano, Italy, during June 04-07, 2024. XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends.  XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. This year’s conference was held with the theme “Reflect, Adapt, Envision”. The 29 papers included in this volume were carefully reviewed and selected from 58 submissions to the following tracks: International Workshop on Advances in Software Intensive Startups Workshop on AI for Agile Software Engineering (AI4ASE) 2nd International Workshop on Global and Hybrid Work in Software Engineering (GoHyb) 11th International Workshop on Large-Scale Agile Development Workshop on the AI Scrum Master: Incorporating AI Into Your Agile Practices and Processes Agile Training and Education Track PhD Symposium Track Posters Track